Absence of t(14;18) chromosome translocation in agricultural workers after short-term exposure to pesticides - Rapisarda, Venerando; Ledda, Caterina; Matera, Serena; Fago, Lucrezia; Arrabito, Giorgio; Falzone, Luca; Marconi, Andrea; Libra, Massimo; Loreto, Carla (Molecular medicine reports, 2017)
Exposure to pesticides represents a potential health risk for the general population and for agricultural workers in particular. Some researchers observed that occupational exposure to pesticides is associated with risk of non-Hodgkins lymphoma (NHL). The chromosomal translocation t(14;18)(q32;q21) is one of the most common chromosomal abnormalities in NHL. The aim of this study was to detect the effects of pesticides on t(14;18) chromosome translocation in agricultural workers after short-term exposure. Fifty-two workers occupationally exposed to pesticides (fungicides and insecticides) and 52 non-exposed were recruited. The farm workers were on average exposed to pesticides for ~3.7 h a day for 5 years. The frequency of BCL2-IGH t(14;18) translocation in workers occupationally exposed to pesticides was 10% (5 of 52) vs. 8% (4 of 52) in the control group. Overall, these data suggest that no significant association between occupational exposure to pesticides and an increased frequency of the chromosomal translocation BCL2-IGH t(14;18) in farmers was observed. However, further studies with a higher number of subjects exposed to pesticides are necessary to confirm this observation.